INCREASING FISCAL AND ECONOMIC RESILIENCE POST PANDEMIC: EVIDENCE FROM SOUTH ASIAN COUNTRIES - Ahmad, Jamil; Alam, Dastgir (Bank Indonesia, 2024)
The South Asia region faced extremely difficult economic challenges from the Coronavirus (COVID-19) pandemic. Almost two billion people living in South Asia were affected by the pandemic. The unprecedented shock in South Asia disturbed the pace and pattern of development and increased the vulnerabilities of the region. The region faced the problems of inequality, high inflation, rising fiscal deficit, disrupted growth, and environmental challenges further increasing the region’s vulnerabilities. Traditional macroeconomic policies are not enough to cope with this problem. In the face of these shocks, South Asian countries need to build robust fiscal and monetary policies and efficient use of remaining resources to build a more resilient economy for the protection of the population. Economic resilience might be effective to overcome such external shocks and support the recovery of all countries especially South Asian countries. Post-pandemic action in South Asian countries thus has become moreimportant, especially with restrained scope of fiscal and monetary stimulus. This examines the impact of COVID-19 on South Asian countries. The paper addresses the economic challenges faced by South Asian Countries in the pre- and post-pandemic period. It also briefly discusses the fiscal stimulus packages released by the South Asian countries to build stronger economies.